APLIKASI UJI KEBERFUNGSIAN DIFERENSIAL UNTUK MENGUJI KETAHANAN BUTIR SKALA PSIKOLOGI TERHADAP RESPONS TIPUAN PADA KONTEKS SELEKSI KERJA - Wahyu Widhiarso (Institute of Research and Community Outreach - Petra Christian University, 2011)
This study aimed to identify items on psychological scale vulnerable to faking responses when it is applied to the employee selection process. Personality scale adaptation of BFI-44 was given to 400 respondents that were divided into two groups. The first group was instructed to respond honestly (neutral condition) while the second group was instructed them as if they are applicants who are follow employee selection test (applicants condition). Differential item functioning (DIF) test with Mantel-Haenzel test was employed. Analysis result suggests that 12 items are vulnerable to faking response that is spread out on four personality factors (extroversion factor, agreeableness, emotional stability and openness to new ideas). Considering on small number of items that indicates DIF, we conclude that measurement of psychological that use self-reporting technique is resistant to faking responses. However, review thoroughly or modification of these items when applied to the job selection process was required.